Respuesta :
Given (x - 3)^2, its trinomial in standard form, y = ax^2 + bx + c:
You must expand the binomial through FOIL method:
(x - 3)^2
x ^2 - 3x - 3x + 9
Combine like terms:
y = x^2 - 6x + 9
where a = 1, b = -6, and c = 9.
Please mark my answer as the Brainliest, if you find this solution helpful :)
You must expand the binomial through FOIL method:
(x - 3)^2
x ^2 - 3x - 3x + 9
Combine like terms:
y = x^2 - 6x + 9
where a = 1, b = -6, and c = 9.
Please mark my answer as the Brainliest, if you find this solution helpful :)